Growing endoprosthesis in management of bone tumours in Malaysia - Saravanan, S.; Vivek, A.S. (Malaysian Medical Association, 2007)
This is to report on the use of growing endoprosthesis, alsoknown as lengthening prosthesis in the management of fourpatients in the paedriatic age group in the OrthopaedicOncolgy Unit at University Malaya Medical Centre. These arecustom made prosthesis, designed and made in India basedon measured roentrograms. The ages of these patients varyfrom 6 to 13 years old. These are cases of Osteosarcoma andEwing’s sarcoma around the knee. This is the first time thesecustom made prosthesis have ever been used in Malaysia.We feel that this is a feasible option for limb salvage in thetreatment of primary bone tumours in growing children.